Pattern of Respiratory Diseases & Associated Socio-Demographic Factors among Workers of Zeal Pak Cement Factory, site area, Hyderabad (Medical Forum Monthly, 2024)
Background: The occupational dust leads to various respiratory diseases. It is a major health problem among factory workers & is under reported in everyday scene of medical practice.Objectives: To assess the frequency of occupation related lung diseases among study population. To seek association of socio-demographic characteristics with occurrence of lung diseases among study population.Study design: Descriptive cross sectional studyPlace and Duration of Study: This study was conducted in the Zeal Pak Cement factory, site area, Hyderabad for a period of one year.Materials and Methods: Data was collected by filling a questionnaire; subjects were selected by convenience sampling. Frequencies were computed, chi-square test was applied to see any statistical analysis of various categorical variables.Results: Among 100 subjects examined, the frequency of respiratory diseases was found among 83% workers. 70% subjects belonged to labour class who were closely exposed to occupational dusts. 58% of the subjects were earning < rs:4000 /month; however no association of socio-economic status was seen with occurrence of respiratory diseases (p=0.06). 63% workers belonged to age group 31-40 years. Chronic bronchitis was the most commonly presenting respiratory disease i.e. 37%, while cor pulmonale reported in 4% of the workers. Silicosis along with tuberculosis was reported among workers of age group 40-50 (p=0.01).Conclusion: The high frequency of occupation dust related respiratory diseases warrants further research in order to design preventive strategies against them.